Effect of silicic acid on aggregation of hydrous ferric oxide - Minh*, Nguyen Ngoc; Picardal, Flynn (Vietnam Journal of Earth Sciences, 2016)
Colloidal properties of hydrous ferric oxide (HFO) have received much attention due to their environmental relevance. In this study, aggregation of HFO was determined by time-resolved dynamic light scattering and test tube experiments, evaluating surface charge via zeta potential (ζ) measurements. The silicic acid charge varies with protonation and deprotonation at different pH levels. As an adsorbing species, silicic acid could modify surface charge and affect the colloidal stability of HFO. Electrophoretic experiments revealed that silicic acid lowered particle ζ, decreased the isoelectric point (iep), and allowed HFO to aggregate at a lower pH. Reversal of charge was observed at pH 7.5, 7.0, 6.4, and 6.2 for silicic acid concentrations of 0, 0.5, 1.0 and 1.5 mM, respectively. By demonstrating that silicic acid shifts the iep of HFO to lower pH values, results indicate that silicic acid can change the aggregation properties of HFO. Both light scattering and test tube experiments revealed a “peak aggregation” at pH 5.5-7.5 in the presence of silicic acid. As this pH range is typical for many aqueous systems and soils, we conclude that silicic acid likely plays an important role in HFO transport in water and accumulation of particulate HFO in soil horizons. References Combes, J.M., Manceau, A., Calas, G., Bottero, J.Y., 1989. Formation of ferric oxides from aqueous solutions: A polyhedral approach by X-ray absorption spectroscdpy: I. Hydrolysis and formation of ferric gels. Geochimica et Cosmochimica Acta 53, 583-594. Cornell, R.M., Schwertmann, U., 1996. The iron oxides: structure, properties, reactions, occurence and uses. VCH, Weinheim and New York. Davis, C.C., Chen, H.-W., Edwards, M., 2002. Modeling Silica Sorption to Iron Hydroxide. Environmental Science & Technology 36, 582-587. Dietzel, M., 2000. Dissolution of silicates and the stability of polysilicic acid. Geochimica et Cosmochimica Acta 64, 3275-3281. Dove, P.M., 1995. Kinetic and thermodynamic controls on silica reactivity in weathering environments. Reviews in Mineralogy and Geochemistry 31, 235-290. Dove, P.M., Rimstidt, J.D., 1994. Silica water interactions - In silica reviews in mineralogy. Mineral Society of America, 29, 259-307. Epstein, E., 2001. Silicon in plants: facts vs. concepts. In: Datnoff, L.E., Snyder, G.H. and Korndörfer, G.H. (Ed.), Silicon in Agriculture. Elsevier, Amsterdam, pp. 1-16. Fortin, D., Langley, S., 2005. Formation and occurrence of biogenic iron-rich minerals. Earth-Science Reviews 72, 1-19. Hiemstra, T., Barnett, M.O., van Riemsdijk, W.H., 2007. Interaction of silicic acid with goethite. Journal of Colloid and Interface Science 310, 8-17. Holthoff, H., Egelhaaf, S.U., Borkovec, M., Schurtenberger, P., Sticher, H., 1996. Coagulation rate measurements of colloidal particles by simultaneous static and dynamic light scattering. Langmuir 12, 5541-5549. Hunter, R.J., 1981. Chapter 3 - The calculation of zeta potential. Zeta potential in colloid science. Academic Press, pp. 59-124. Icopini, G.A., Brantley, S.L., Heaney, P.J., 2005. Kinetics of silica oligomerization and nanocolloid formation as a function of pH and ionic strength at 25°C. Geochimica et Cosmochimica Acta 69, 293-303. Iler, R.K., 1979. The chemistry of silica. Wiley-Interscience, New York. Karathanasis, A.D., 2002. Mineral equilibria in environmental soil systems, in: Soil Mineralogy with environmental applications. Soil Science Society of America, 109-151. Kretzschmar, R., Holthoff, H., Sticher, H., 1998. Influence of pH and humic acid on coagulation kinetics of kaolinite: A dynamic light scattering study. Journal of Colloid and Interface Science 202, 95-103. Kuma, K., Nakabayashi, S., Suzuki, Y., Matsunaga, K., 1992. Dissolution rate and solubility of colloidal hydrous ferric oxide in seawater. Marine Chemistry 38, 133-143. Lagaly, G., Schulz, O., Ziemehl, R., 1997. Dispersionen und emulsionen: Eine Einführung in die Kolloidik feinverteilter Stoffe einschließlich der Tonminerale. . Steinkopff Verlag, Darmstadt. Li, H., Shan, C., Zhang, Y., Cai, J., Zhang, W., Pan, B., 2016. Arsenate adsorption by hydrous ferric oxide nanoparticles embedded in cross-linked anion exchanger: Effect of the host pore structure. ACS Applied Materials & Interfaces 8, 3012-3020. Lindsay, W.L., 1979. Chemical equilibria in soils. Wiley, New York. Lützow, M.v., Kögel-Knabner, I., Ekschmitt, K., Matzner, E., Guggenberger, G., Marschner, B., Flessa, H., 2006. Stabilization of organic matter in temperate soils: mechanisms and their relevance under different soil conditions - a review. European Journal of Soil Science 57, 426-445. Mori, Y., Togashi, K., Nakamura, K., 2001. Colloidal properties of synthetic hectorite clay dispersion measured by dynamic light scattering and small angle X-ray scattering. Advanced Powder Technology 12, 45-59. Nguyen, N.M., Dultz, S., Tran, T.T.T., Bui, T.K.A., 2013. Effect of anions on dispersion of a kaolinitic soil clay: A combined study of dynamic light scattering and test tube experiments. Geoderma 209-210, 209-213. Pike, E.R., Abbiss, J.B., 1997. Light scattering and photon correlation spectroscopy. Springer Science + Business Media, B.V. Rothbaum, H.P., Rohde, A.G., 1979. Kinetics of silica polymerization and deposition from dilute solutions between 5 and 180°C. Journal of Colloid and Interface Science 71, 533-559. Sommer, M., Kaczorek, D., Kuzyakov, Y., Breuer, J., 2006. Silicon pools and fluxes in soils and landscapes-a review. Journal of Plant Nutrition and Soil Science 169, 310-329. Spadini, L., Schindler, P.W., Charlet, L., Manceau, A., Vala Ragnarsdottir, K., 2003. Hydrous ferric oxide: evaluation of Cd-HFO surface complexation models combining CdK EXAFS data, potentiometric titration results, and surface site structures identified from mineralogical knowledge. Journal of Colloid and Interface Science 266, 1-18. Svensson, I.L., Sjoberg, S., Ohman, L.O., 1986. Polysilicate equilibria in concentrated sodium silicate solutions. J. Chem. Soc., Faraday Trans. 1 82, 3635-3646. Towe, K.M., Bradley, W.F., 1967. Mineralogical constitution of colloidal “hydrous ferric oxides”. Journal of Colloid and Interface Science 24, 384-392. Wonisch, H., Gérard, F., Dietzel, M., Jaffrain, J., Nestroy, O., Boudot, J.P., 2008. Occurrence of polymerized silicic acid and aluminum species in two forest soil solutions with different acidity. Geoderma 144, 435-445.